Current debates in urban theory from a scale perspective: Introducing a scenes approach. (June 2019) - Wu, Cary; Wilkes, Rima; Silver, Daniel; Clark, Terry Nichols
Cities, all over the world, have become more diverse than ever. This poses great challenges to urban studies and theorising. In this article, we review current debates in urban theory through Howitt's (1998) three-facet conceptualisation of geographical scale and find that urban theorists have high levels of disagreement on the areal (scale as size), the hierarchical (scale as level) as well as the dialectical (scale as relation) aspects of the city. We show that, if urban theorists are to find a common approach to the city, we should contemplate: 1) what cities to study; 2) from which geographical level(s); and 3) how the city relates to other entities. We illustrate how the theory of urban scenes could potentially be used to address these debates in urban theory.